Academic procrastination in Ecuadorian university students: An explanatory model based on academic motivation - Xavier Fabricio Reyes Trelles; Pedro Israel Alvarado Cevallos; Katherine Paola Calle Torres; Jhessenia Natalia Galarza Parra (Heliyon)
Academic procrastination is a multifaceted variable that encompasses different affective, cognitive, and behavioral factors, and has a high incidence in university students with important negative academic, personal, and social consequences. As such, this study aims to explain the levels of academic procrastination in relation to academic motivation and certain sociodemographic variables. The sample was composed of 117 students belonging to the University of Cuenca, Ecuador, they completed a questionnaire of sociodemographic variables, academic motivation scale and academic procrastination scale. Results showed high levels of intrinsic and extrinsic motivation, as well as low levels of amotivation, together with a medium level of total academic motivation and academic procrastination in the participants. The logistic regression model with ordinal response evidenced a 19 % reduction in fit when considering the dimensions of intrinsic motivation, extrinsic motivation, and amotivation, only intrinsic motivation was statistically significant in explaining academic procrastination, while total academic motivation and sociodemographic variables did not contribute significantly to the model. These findings confirm the importance of academic motivation, mainly intrinsic motivation, in the understanding of academic procrastination. The theoretical and practical implications of the results are discussed, highlighting their relevance in explaining this phenomenon and benefiting students.